GIONGO BAHASA JEPANG PADA KOMIK ONE PIECE - Tamara Fernanda Ricardo; Arza Aibonotika; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The aim of this study was to identify the type and meanings of Japanese onomatopoeia in One Piece comic. The qualitative descriptive methods of this study used phonology and morphology to explain the sounds of onomatopoeia. The data in this study is onomatopoeia words of the giongo type. Onomatopoeia is divided by sound replication from inanimate objects which is nature and treated objects. Giseigo is divided by onomatopoeia that replicate animal sound and human voice. There are several forms of onomatopoeia, namely basic words, germinate consonant (sokuon) is a clipped sound, or slight pause, when pronouncing the word in Japanese, nasal phoneme (hatsuon) described the reverberate of onomatopoeia, long vowels (chou'on) is a word that have long sounds resulting in a lengthened pronunciation in Onomatopoeia, and reduplication (hanpukukei) also represented the onomatopoeia sounds that are usually repeated.Key Words: Giongo, One Piece, Onomatope